Religious Ideology and Cultural Fantasy: Catholic and Anti-Catholic Discourses in Early Modern England - Baumstein, Paschal (Cistercian studies quarterly, 2006)
The article reviews the book "Religious Ideology and Cultural Fantasy: Catholic and Anti-Catholic Discourses in Early Modern England," by Arthur F. Marotti.